Financial Performance Analysis Using Economic Value Added (EVA) Method (Case Research at PT. Taman Wisata Candi Borobudur, Prambanan dan Ratu Boko (Persero)) - Fidi Hidayati; Yacobo P Sijabat (Universitas Binaniaga Indonesia, 2022)
Abstract. The research was conducted with the aim of analyzing the financial performance of PT. Borobudur, Prambanan & Ratu Boko (Persero) Temple Tourism Parks for the period 2019 and 2020. The research data was obtained from documentation using NOPAT analysis tools, capital costs, and Economic Value Added (EVA) analysis. The type of data used in this study is quantitative data, namely data in the form of numbers in the true sense. The source of data in this study is secondary data. The results of this study indicate that using the Economic Value Added (EVA) method in the research period has been able to provide added economic value for the company as evidenced by the value of the calculation results, namely the EVA value > 0 is positive. Keywords: Net Operating After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital, Capital Charges, and Economic Value Added (EVA).